Upaya Penggalangan Satuan Intel Dalam Mencegah Berkembangnya Paham Radikal - Joshua Cavin (Indonesian Journal of Police Studies, 2020)
The criminal act of terrorism itself has a concept called radical originating from Latin namely radix and radici which means 'root' or 'source', in a broader sense this radical term refers to basic things, fundamental principles , or bias also means 'unusual' or unconventional. The Purwakarta Police Intelligence Unit as the executor of the IV Quick Wins program in 2020 is one of the National Police territorial units assigned to form and streamline Polri Ops Task Force counter-radical and deradicalizing (specifically ISIS). In this study the authors wanted to find out and analyze the application of management functions in the implementation of raising, obstacles encountered in raising efforts, as well as creative efforts made by Purwakarta Police Intelligence Unit in conducting a drive. The study was conducted with a qualitative approach with explorative qualitative research methods. Primary and secondary data sources with data collection techniques used are through interviews, observations and study documents located in the jurisdiction of the Purwakarta Police Resort. The analysis used data reduction, data presentation and drawing conclusions or verification. The conclusion of this study is that the efforts made are quite good but not optimal because the personnel who have the expected qualifications are still very minimal, the lack of mastery of Intelligence's special equipment by personnel, there is no rules of cooperation that causes contact with Detachment 88 AT, and the lack of Cooperation with related agencies to be able to mobilize terrorist convicts in Purwakarta. Suggestions given by researchers are the submission of the names of personnel who have been incorporated in a spy ops units for radical activity to be able to participate in vocational education specializing in raising and detecting radical groups, sending personnel to attend Intelligence's special equipment or technology Intelligence training, making rules of cooperation clear with Detachment 88 AT's job description that is implemented does not touch each other, and builds Collaboration with the Purwakarta Penitentiary to make activities in the context of raising and de-radicalizing the terrorist convicts.